Sleep duration and quality in elite athletes measured using wristwatch actigraphy - Leeder, J.; Glaister, M.; Pizzoferro, K.; Dawson, J.; Pedlar, C. (Journal of Sports Sciences, 2012)
Sleep is known to be an important component of recovery from training, yet little is known about the quality and quantity of sleep achieved by elite athletes. The aim of the present study was to quantify sleep in elite athletes using wristwatch actigraphy. Individual nights of sleep from a cohort of Olympic athletes (n = 47) from various sports were analysed and compared to non-athletic controls (n = 20). There were significant differences between athletes and controls in all measures apart from `time asleep` (p = 0.27), suggesting poorer characteristics of sleep in the athlete group. There was a significant effect of gender on `time awake` (mean difference: 12 minutes higher in males; 95% likely range: 3 to 21 minutes) and `sleep efficiency` (mean difference: 2.4 lower in males; 95% likely range: 0.1 to 4.8). Athletes showed poorer markers of sleep quality than an age and sex matched non-athletic control group (Sleep efficiency: 80.6 ± 6.4% and 88.7 ± 3.6%, respectively. Fragmentation Index: 36.0 ± 12.4 and 29.8 ± 9.0, respectively) but remained within the range for healthy sleep. This descriptive study provides novel data for the purpose of characterising sleep in elite athletes.